Factors Influencing Adherence to Ethical Values: A Case Study of Accountants in the Zambian Public Sector - Nalukui Simushi; Bupe Getrude Mutono Mwanza (International Journal of Engineering and Management Research, 2022)
Financial scandals continue to negatively impact businesses all over the globe with Zambia not being an exception. The financial accounts of businesses are handled by accountants who are members of professional bodies and are governed by a code of ethics put in place to regulate professional conduct. This study aimed to establish the relationship between factors influencing ethical values and the accountants’ adherence to the code of ethics. The study employed a quantitative approach with the use of structured questionnaires on a population sample comprising of finance and accounting staff from the Zambian public sector. To determine the respondents, simple random sampling was used to identify the population of interest. The outcome from the study showed remuneration of accountants, internal controls within organisations and independence of accountants to be among the factors that influence adherence to ethical values. It was found that there is a positive relationship between remuneration of accountants, internal controls, independence of accountants and the accountants’ adherence to ethical values. It is therefore expected that the higher the remuneration of the accountant, the stronger the internal controls, the higher the independence of the accountant, the easier it is for the accountant to adhere to ethical values. This study contributes towards enhancing measures put in place to address the shortcomings attributed to compliance with the code of ethics for public sector accountants. It will also be beneficial to accountants as it will echo the need for accountants to uphold ethical values.